Eksistensi Paralegal dalam Meminimalisir Kekerasan Terhadap Perempuan di Desa Tuwed Kabupaten Jembrana - I Nyoman Gede Sugiartha; Cokorde Gede Swetasoma (Kertha Wicaksana, 2022)
The existence of paralegals in increasing public legal awareness has been widely studied. One of the important roles of paralegals in Bali, especially in Tuwed Village, Melaya District, Jembrana Regency, is to minimize violence against women which is still found in Bali, which is famous for upholding patrilineal lineages where there is an assumption that the position of men is higher than women. This happens due to a lack of knowledge about the law, especially for the poor and marginalized. After the birth of paralegals as an implementation of Law Number 16 of 2011 concerning Legal Aid, it is very interesting to study its relation to violence against women. The problem is how the existence of paralegals in minimizing cases of violence against women in Tuwed Village, Melaya District, Jembrana Regency and how paralegals' efforts in increasing legal awareness to prevent violence against women in Jembrana Regency. In this study, the authors use empirical research methods with a case study approach in examining the existence of paralegals in preventing violence against women as regulated in the Law on Legal Aid Number 16 of 2011 concerning Legal Aid. The results of this study indicate that the existence of paralegals in preventing violence against women in Tuwed Village, Jembrana Regency is effective, because there has been an increase in legal awareness from the community and socialization about paralegals and violence against women to the people of Jembrana Regency.